Disenfranchised Grief Following African American Homicide Loss: An Inductive Case Study. (March 2015) - Piazza-Bonin, Elizabeth; Neimeyer, Robert A.; Burke, Laurie A.; McDevitt-Murphy, Meghan E.; Young, Amanda
Disenfranchised grief is experienced when a mourner's grief response is socially invalidated, unacknowledged, or discouraged. When the circumstances of death or the emotional reactions of the griever violate social norms, empathic failures can occur within the bereaved individual's support systems. This study used conventional content analysis, an intensive and inductive qualitative research method, to analyze the experience of one African American woman who lost her only son to homicide, a particularly distressing and marginalized form of loss. Results elucidate both the empathic failings and resiliencies within the social systems of this griever and emerged from the perspectives offered by the bereaved mother and her primary supporter. Clinical implications and suggestions for future research are discussed.